EFFECT OF HIGH-FAT DIET ON SERUM TNF-ALPHA LEVELS, A MARKER OF LOW-GRADE INFLAMMATION - Cut Indriputri (Universitas Airlangga, 2024)
A high-fat diet is a pattern of excessive fat consumption that can cause various metabolic function disorders, such as hypertension, dyslipidemia, obesity, and increased glucose levels. The aim of this study was to analyze the effect of a high-fat diet on serum tumor necrosis factor alpha (TNF-α) levels as a marker of low-grade inflammation in Wistar rats. The study was designed using a true experimental randomized posttest-only control group. Sixteen male Wistar rats weighing 150-250g and aged 4-5 months were divided into two groups. Group K1 was a negative control group that was given normal diet, while group K2 was a group that was given a high-fat diet, with a fat content of 66.28%. This treatment was controlled for 50 days. The mean TNF-α levels in K1 (290.912 ± 1.87) pg/mL and K2 (295.149 ± 2.76) pg/mL. Based on the results of independent T-test analysis, TNF-α levels in groups K1 and K2 were significantly different (P = 0.034 or P < 0.05). This means that a high-fat diet increases serum levels of TNF-a, a marker of low-grade inflammation.